2022
DOI: 10.1177/01454455221113560
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Acceptability of Telehealth-Based Coaching for Caregivers in Asian Countries

Abstract: Recent studies evaluating the effectiveness of using telehealth to train caregivers across large geographical distances in the United States and internationally indicate that this modality can increase families’ accessibility to evidence-based interventions for problem behavior. In this study, experimenters and interpreters in the United States remotely coached nine caregivers of children with disabilities residing in three countries in Asia to implement functional analyses (FA) and functional communication tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Hence, telehealth was widely explored as a practical option to deliver interventions for children with NDDs in many settings, especially in HICs (Rosenbaum et al, 2021). However, telehealth as an established method of service delivery is less reported in the Asia‐Pacific region (Vikram et al, 2021), yet recent evidence supports telehealth as a successful and an acceptable modality to deliver parent coaching to implement parent‐mediated services from the Asian region (Tsami et al, 2019; Tsami et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, telehealth was widely explored as a practical option to deliver interventions for children with NDDs in many settings, especially in HICs (Rosenbaum et al, 2021). However, telehealth as an established method of service delivery is less reported in the Asia‐Pacific region (Vikram et al, 2021), yet recent evidence supports telehealth as a successful and an acceptable modality to deliver parent coaching to implement parent‐mediated services from the Asian region (Tsami et al, 2019; Tsami et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have demonstrated the efficacy of using telehealth technologies to train caregivers and professionals who are geographically distant from the trainer (Frieder et al, 2009;Lee et al, 2015;Tomlinson et al, 2018). This approach has been particularly useful for disseminating evidence-based interventions to families and professionals across the globe (e.g., Neely et al, 2019;Tsami et al, 2019Tsami et al, , 2023Zhu et al, 2020). In Tsami et al (2023), for example, experimenters in the United States remotely coached nine caregivers of children with ASD and other disabilities residing in Pakistan, Vietnam, and India to implement functional analyses and treatments for severe problem behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been particularly useful for disseminating evidence-based interventions to families and professionals across the globe (e.g., Neely et al, 2019;Tsami et al, 2019Tsami et al, , 2023Zhu et al, 2020). In Tsami et al (2023), for example, experimenters in the United States remotely coached nine caregivers of children with ASD and other disabilities residing in Pakistan, Vietnam, and India to implement functional analyses and treatments for severe problem behavior. The training was highly effective for all parents and resulted in dramatic reductions in problem behavior for all but one child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The special issue starts with an article demonstrating the global reach of behavioral interventions through telehealth (Tsami et al, 2023). Tsami et al evaluated the effectiveness of using telehealth to train caregivers of children with disabilities residing in three countries in Asia with limited access to behavior-analytic services.…”
mentioning
confidence: 99%